Valorización de los activos de la empresa Primefenix S. A. - Torres Palma, Luis Pedro (2021)
This essay aims to analyze the Valuation of Assets, defining each word in its concept, and it also explains it through a practical case applied to the company Primefenix S. A ”. Applying a simple methodology that can teach the clear process that this entity would have in its valuation of fixed assets, using techniques that are efficient.